North child - Pattou, Edith (London Usborne, 2012)
A luxury edition of Edith Pattou's epic tale of love, courage and destiny. Rose has fallen in love with an enchanted stranger and must journey to the land east of the sun to free him. This magical and moving tale has been shortlisted for the Ottaker's Children's book prize and St. Helens Young Books Awards 2012. A perfect gift
Keywords: Children's stories -- Fantasy fiction -- Bears